Plato in the Third Sophistic - Fowler, Ryan C. (Millennium-Studien / Millennium Studies, 2014)
Plato in the Third Sophistic examines the influence and impact of Plato and Platonism in the era of Byzantine and Christian rhetoric. The volume brings together articles from leading scholars of late antique philosophy and literature. Their examinations show that Plato is the single most important and influential literary figure used to frame the literature of this time.